Párhuzamos halálrajzok . Parallel Death Patterns - Jeles, András (Hunnia Filmstúdió, 2008)
Verzio FF Duration: 02:12:00 The film draws parallels between two recent tragic events and the stories of the people involved: the first is the story of an ornithologist, Lajos Sz., lynched in front of his daughters in the village of Olaszliszka in 2006; the second, that of a 13-year-old boy suffering from leukemia and the tribulations of his parents following his death in a Budapest hospital.